(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Vaginismus is a female sexual disorder characterized by reflex contractions of the muscle group going from the pubic bone to the coccyx, causing the muscles in the pelvis to become tense suddenly, not allowing any movement. Due to its rarity and poorly understood pathophysiology, the diagnosis and management of vaginismus is challenging. Aim: To report the case of primary vaginismus. Methods: A case with is vaginismus presented including subjective reporting, clinical findings, diagnostics, and follow-up are presented. Female sexual function index (FSFI) was recorded before and after treatment. The patient’s consent was explained and signed before treatment. Results:We present a case of a 33-year-old woman with a vaginismus treated by Sex education, Psychotherapy and Sex therapy. The patient had penetrative sex after 5 treatment sessions. The FSFI score increased from 4 point to 24,4 point after treatment. No complications were recorded during treatment. Conclusions: Sex education, Psychotherapy and Sex therapy seems as a safe and successful, low-cost methods of treating primary vaginismus.